Effect of capillary pressure on performance of a heat pipe: Numerical approach with FEM - Nat Thuchayapong (2018)
Heat pipes are devices capable of very high heat transfer and have been widely used in many thermal management applications. Nevertheless, both the understanding and design of heat pipe operations could benefit from further developments of numerical simulations. In this study, two-dimensional heat transfer and fluid flow in a heat pipe at steady state was numerically simulated using the Finite Element Method (FEM). The calculated domains consisted of a vapor core, wick, wall of container, and water jacket. The capillary pressure model was used for the liquid-vapor interface in the wick. The capillary radius variation was assumed to be a simple linear function and applied in the capillary model. This assumption was used for investigating the effect of capillary pressure on performance of a heat pipe. It also affected on the wall temperature distributions at the end of evaporator section. To confirm the validity of the simulations, the vapor and wall temperature distribution results were compared with experimental data of heat pipes with the copper-mesh wick obtained by Huang et al. Our numerical results indicate that the capillary pressure gradient inside the wick at the end of the evaporator section was very large. This may have been a result of fast liquid motion at the end of the evaporator section, thus, providing efficient heat transfer through convection. In conclusion, experimentally-validated heat pipe temperature distributions were successfully simulated in two dimensions, which may help improve the accuracy and efficiency of heat pipe design. © 2011 Elsevier Ltd. All rights reserved.